Human cytochromes P450 1A1 and 1A2 participate in detoxication of carcinogenic aristolochic acid - Sistkova, Jana; Hudecek, Jiri; Hodek, Petr; Frei, Eva; Schmeiser, Heinz H; Stiborova, Marie (Neuro endocrinology letters, 2008)
OBJECTIVES: A carcinogenic and nephrotoxic plant alkaloid, aristolochic acid (AA), causes the development of aristolochic acid nephropathy, which is characterized by chronic renal failure, tubulointerstitial fibrosis and urothelial cancer. AA may also cause a similar type of kidney fibrosis with malignant transformation of the urothelium, the Balkan endemic nephropathy. The aim of the study was to resolve which cytochromes P450 (CYP) detoxicate the major component of AA, aristolochic acid I (AAI), to its O-demethylated metabolite, aristolochic acid Ia (AAIa). METHODS: High performance liquid chromatography (HPLC) was employed for separation and characterization of AAI metabolites generated by CYPs. RESULTS: Human, rat and mouse hepatic CYPs oxidize AAI into its detoxication metabolite AAIa. Most of the detoxication of AAI in human hepatic microsomes is mediated by CYP1A2 and 1A1, while other CYPs play a minor role. CONCLUSIONS: The data are the first report on identification of human CYP enzymes detoxicating AAI.
Keywords: Microsomes, Liver; Cytochrome P-450 CYP1A2; Inactivation, Metabolic; vysokoúčinná kapalinová chromatografie; Cytochrome P-450 CYP1A1; metabolická inaktivace; cytochrom P-450 CYP1A1; Aristolochic Acids; Chromatography, High Pressure Liquid; krysa rodu Rattus; cytochrom P-450 CYP1A2; kyseliny aristolochové; Animals; lidé; Carcinogens; Humans; karcinogeny; zvířata; Rats; myši inbrední C57BL; myši; Mice, Inbred C57BL; Mice; jaterní mikrozomy